TLR2-independent induction and regulation of chronic intestinal inflammation. - Boulard, O; Asquith, M; Powrie, F; Maloy, K (2010)
Interactions between the intestinal microflora and host innate immune receptors play a critical role in intestinal homeostasis. Several studies have shown that TLR2 can modulate inflammatory responses in the gut. TLR2 signals enhance tight junction formation and fortify the epithelial barrier, and may play a crucial role in driving acute inflammatory responses towards intestinal bacterial pathogens. In addition, TLR2 agonists can have direct effects on both Th1 cells and Treg. To define the role of TLR2 in the induction and regulation of chronic intestinal inflammation we examined the effects of TLR2 deletion on several complementary models of inflammatory bowel disease. Our results show that TLR2 signals are not required for the induction of chronic intestinal inflammation by either innate or adaptive immune responses. We further show that TLR2(-/-) mice harbor normal numbers of Foxp3(+) Treg that are able to suppress intestinal inflammation as effectively as their WT counterparts. We also did not find any intrinsic role for TLR2 for pathogenic effector T-cell responses in the gut. Thus, in contrast to their role in acute intestinal inflammation and repair, TLR2 signals may have a limited impact on the induction and regulation of chronic intestinal inflammation.